Riboflavin supplementation and biomarkers of cardiovascular disease in the elderly - Tavares, NR (2009)
High levels of total plasma homocysteine are potentially harmful in the elderly. To investigated the effects of oral riboflavin supplementation on plasma total homocysteine, ferritin, uric acid and C-reactive protein concentration in elderly people with a low riboflavin status. We performed a four-week randomized, placebo-controlled, double-blind trial of riboflavin supplementation in seven Portuguese day social centers. Eighty-eight individuals (66.7% female), aged between 60 and 94 years, volunteered to participate in the study following interview. Forty-two subjects, with an erythrocyte glutathione reductase activation coefficient (EGRAC) 1.2, were included in the intervention trial. All subjects gave informed consent. Study subjects were administered 10 mg riboflavin (n=21) or placebo (n=21) each day for 28 days. Riboflavin supplementation significantly decreased plasma tHcy (P=0.005) and EGRAC (P=0.014), but not plasma ferritin, uric acid or C-reactive protein. In this elderly group, we found that 10 mg/day oral riboflavin supplementation lowered plasma homocysteine concentrations in subjects with low riboflavin status.